2021
DOI: 10.21203/rs.3.rs-180649/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Utilization of Whey for Red Pigment Production by Monascus Purpureus in Submerged Fermentation

Abstract: Various biotechnological approaches have been employed to convert food waste into the value-added bioproducts through fermentation processes. Whey, a major waste generated by dairy industries, is considered an important environmental pollutant due to its massive production and high organic content. The purpose of this study is to produce red color pigment from whey by using Monascus purpureus. The submerged culture fermentation parameters have been optimized to produce the red Monascus pigment. Demineralized (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Figure 5 shows that by increasing peptone concentration, the amount of pigment decrease. Mehri et al ( 2021 ) found that the pigment production increased linearly up to 25 g/L of MSG concentration resulting in a maximum pigment synthesis of 45.7 UA 510nm and then declined at higher monosodium glutamate (MSG) concentrations. Raman et al ( 2015 ) found that decreasing the concentration of nitrogen source in the production medium of melanin by Aspergillus fumigatus AFGRD105 has a positive effect on pigment production.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 shows that by increasing peptone concentration, the amount of pigment decrease. Mehri et al ( 2021 ) found that the pigment production increased linearly up to 25 g/L of MSG concentration resulting in a maximum pigment synthesis of 45.7 UA 510nm and then declined at higher monosodium glutamate (MSG) concentrations. Raman et al ( 2015 ) found that decreasing the concentration of nitrogen source in the production medium of melanin by Aspergillus fumigatus AFGRD105 has a positive effect on pigment production.…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported that M. ruber growth rates were higher at pH 6.0 in culture medium containing 20 g L À1 of whey powder. Mehri et al (2021) studied the effect of whey type as a substrate on pigment production. The authors used demineralized whey powder, deproteinized whey powder, raw whey powder, treated deproteinized raw whey powder and treated deproteinized demineralized whey powder for production of pigments using Monascus purpureus and reported that maximum pigment production was (20.8 UA) at 510 nm using demineralized whey.…”
Section: Yeasts and Fungimentioning
confidence: 99%
“…Whey does not require so many pre-treatments prior to fermentation and is considered as more economical and sustainable alternative within circular economy for the production of natural pigments. The operational cost of production of red pigments by M. purpureus was 14.92 dollars/kg using demineralised whey as a substrate (Mehri et al, 2021).…”
Section: Production Costmentioning
confidence: 99%
“…In addition to the products highlighted above, recent efforts in the microbial valorization of whey have included production of pigments (Mehri et al., 2021 ); enzymes such as β-galactosidases (Bentahar et al., 2019 ) and lipases (Knob et al., 2020 ); and polymers such as bacterial exopolysaccharides, bacterial cellulose, and chitosan (Kolesovs & Semjonovs, 2020 ; Kuppamuthu et al., 2020 ; Li et al., 2020 ). Collectively, these results demonstrate that both sweet and acid whey are feedstocks of interest for valorization.…”
Section: Carbohydrate-rich Food Wastesmentioning
confidence: 99%